Keanekaragaman dan Kelimpahan Vegetasi Riparian di Sungai Saroka Kecamatan Saronggi Kabupaten Sumenep - Ali, Mahrus; Wulandari, Sri Riani; Ferdiansyah, Akhmad (Fakultas Matematika & Ilmu Pengetahuan Alam - Universitas Islam Malang, 2024)
Riparian vegetation is a plant community of several types of habitus such as trees, saplings and seedlings that live on river banks. The characteristics of riparian vegetation which have specifically adapted to environmental conditions make it have many strategic functions in maintaining the ecosystem. Some of the positive impacts of riparian vegetation depend on the varying structure and composition of the vegetation. The destruction of riparian vegetation will result in a decrease in the function of riparian vegetation in maintaining the ecosystem. The aim of this research is to study the diversity and abundance of riparian vegetation and to study environmental factors that influence the diversity and abundance of riparian vegetation. The method used is the belt transect method. The method is to make 4 belt transects, each measuring 10m x 80m. Each belt transect is made into a quadrant measuring 10m x 10m which is installed perpendicular to the river bank. Each quadrant is placed with a sampling plot measuring 2m x 2m for seedlings, 5m x 5m for saplings, and 10m x 10m for trees. Vegetation analysis includes: importance value index, diversity index (H'), uniformity index (E), and dominance index (C). The research was conducted on the Saroka River, Saronggi District, Sumenep Regency. The results of this research were the discovery of 37 types of riparian vegetation from 20 families whose habit was trees, saplings and seedlings. The highest INP for tree habitus is dominated by banana species, sapling habitus is dominated by cassava, while INP for seedling habitus is puzzle. The diversity index at all research stations is moderate (H'= 2.12), the uniformity index is high (E= 0.75) with a dominance index of 0.17 (almost no individuals dominate). Environmental factors that influence the diversity and abundance of riparian vegetation are air humidity, soil pH and environmental temperature.